Aggressive fibromatosis in the submandibular region of a child. Issue 4 (20th April 2022) - Alam, Mostafa; Mir Mohammad Sadeghi, Hassan; Mashhadiabbas, Fatemeh; Iranparvar Alamdari, Mina
Abstract: Aggressive fibromatosis is proliferation of well‐differentiated fibroblasts. Submandibular region is rare location for fibromatosis. We report a case of a rapidly growing mass in submandibular region of 5‐year‐old girl, excised surgically and ascertained to be aggressive fibromatosis on histological examination. Recovery was uneventful, and she was disease‐free in 6‐month follow‐up. Abstract : Fibromatosis is a soft tissue tumor with nonspecific clinical features. Bone erosion with periosteal reaction creates a challenge in radiographic interpretation of soft tissue lesion. Histopathological examination is essential for diagnosis.